Decomposition of wood, petiole and leaf litter by Xylaria species from northern Thailand - Takashi Osono (2018)
Ten Xylaria isolates (five obtained from wood and five from leaf litter) collected in northern Thailand were tested for their ability to decompose 13 types of wood, petiole, and lamina from seven tropical tree species under pure culture conditions. The mass loss of the 13 substratum types caused by the 10 Xylaria isolates ranged from 1.2. % to 37.4. % of the original mass. The substratum, the origin of isolates, and the contents of lignin, total carbohydrates, and nitrogen in substrata affected the mass loss. Mass loss was generally in the order: petiole > lamina > wood. Overall, the strains isolated from wood caused greater mass loss than the strains isolated from litter. The mass loss caused by the 10 Xylaria isolates was negatively affected by lignin and total carbohydrate contents, and positively correlated with nitrogen content of the substrata. The values of mass loss in wood in the present study were in the same range as those reported for other Xylaria isolates in previous studies, whereas the mass losses in leaf litter were generally higher than those of previous results, which is partly due to the relatively low lignin contents in leaf litter used in the present study. © 2010 Elsevier Ltd and The British Mycological Society.